Exploration of 1, 2-naphthoquinone-4-sulfonate derivatizing reagent for determination of chlorthalidone in tablets: a spectrophotometric investigation - Suraj R. Chaudhari; Atul A. Shirkhedkar (SpringerOpen, 2021)
Abstract Background Chlorthalidone is a diuretic medicinal agent used to treat hypertension. Lowering hypertension results in the prevention of strokes, heart attacks and kidney-related problems. Results In this work, the spectrophotometric investigation was employed to examine the reaction between chlorthalidone and 1, 2-naphthoquinone-4-sulfonate. A reaction is performed at the alkaline environment (pH 9.2) and heated at a moderate temperature of 60 ± 1 °C using a water bath. The red colour product was produced, and it displayed a maximum absorbance at 440.50 nm. Further, the advancement of response conditions was explored by UV/visible spectrophotometer. The stoichiometric of the reaction was considered by using Job's plot and the reaction mechanism of the proposed work was drawn. The established approach obeyed the calibration curve in the concentration range of 2-12 μg/mL with a regression coefficient superior to 0.994. The accuracy of the method, assessed by employing the % recovery, was in the range of 99.06-99.60% with the % relative standard deviation being less than 2%. The limit of detection and limit of quantification were 0.58 μg/mL and 1.72 μg/mL, respectively. Conclusion A UV/visible spectrophotometric investigation for the analysis of the chlorthalidone in the tablet matrix was successfully established and validated. The established investigation was found to be simple and accurate, and because of its ease of use, the proposed strategy could be applied for quality control investigation of chlorthalidone in pharmaceutical matrices.